Pre-andean serpentinite-chromite orebodies in the Eastern Cordillera of Central Perú, Tarma province - Castroviejo Bolibar, Ricardo (2009)
Ultramafic rocks occur scattered along a 300 km long NNW-SSE trending belt, lying parallel to the central Peruvian Andean direction in the Cordillera Oriental, from Tarma (Junín Dept.) to Huánuco and Tingo María (Huánuco Dept.). The Tarma occurrences (Tapo and Acobamba) are studied, as first step of a broader research. The Tapo massif comprises strongly tectonised serpentinites with scarce peridotitic relics, amphibolites and podiform chromitites. It is overthrust on the lower carboniferous metasediments of the andean basement (Ambo Group), and it shows evidences of a pre-andean deformational history, not found in the Ambo Group; the basal thrust plane is folded by Andean tectonics. The two smaller Acobamba occurrences are also allochtonous and show similar tectonic characteristica. Major and trace element compositions of the amphibolites point to a tholeiitic basalt (to picrobasalt) protolith, compatible with an ocean ridge or ocean island environment. Small scale mining worked podiform chromitite lenses and chromite disseminations, strongly deformed, metamorphosed and overprinted by hydrothermal alteration related to deformation. The ores comprise mainly chromite, ferritchromite, spinel, magnetite, ilmenite and scarce sulphides, as well as the secondary minerals stichtite and nimite. Results of this work exclude current interpretations of the Tarma ultramafites as autochtonous igneous intrusives.